1985
DOI: 10.4148/2378-5977.2442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenbendazole on cow-calf performance and fecal egg counts (1985)

Abstract: A field trial was conducted with 80 cow-calf pairs to evaluate the effect of deworming both cows and calves with fenbendazole, on cattle performance and internal parasite burden. Midseason and weaning weights of calves in the fenbendazole-treated group averaged 22.4 and 33.5 lb heavier (P<.04), respectively, than controls. Cow and calf fecal egg counts were low throughout the grazing season and were not materially affected by treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Although adjusted calf weaning weight for calves from dewormed cows averaged 200.6 vs 197.2 kg from untreated cows, this difference was not significant. Several studies have shown that performance of dewormed nursing calves increased (Ciordia et al, 1984;Kuhl et al, 1985). Other research (Strohbehn et al, 1990), in agreement with data in this paper, failed to detect a significant response.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although adjusted calf weaning weight for calves from dewormed cows averaged 200.6 vs 197.2 kg from untreated cows, this difference was not significant. Several studies have shown that performance of dewormed nursing calves increased (Ciordia et al, 1984;Kuhl et al, 1985). Other research (Strohbehn et al, 1990), in agreement with data in this paper, failed to detect a significant response.…”
Section: Resultssupporting
confidence: 89%
“…One of the most widespread Beef, Cows, health problems for ruminants on a worldwide basis is the presence of internal parasites (Armour, 1980;Borgsteede and Burg, 1982). The level of infection and its effect on animal performance in the U.S. and Canada has been documented in certain areas by numerous researchers, including Levine and Aves (1956); Zimmerman and Hubbard (1961); Cox and Todd (1962); Jacobson and Worley (1 969); Ferguson et al (1971); Leland et al (1973); Ciordia (1975); Ward et al (1979); Wescott et al (1979); Baker et al (1981); Block et al (1985);Kuhl et al (1985, andKnox (1989).…”
Section: Introductionmentioning
confidence: 97%